The Role of Forensic Accounting in Fraud Prevention efforts in Indonesia - Atang Hermawan (Journal of Economics and Business (JECOMBI), 2022)
This study aims to analyze the role of forensic accounting in efforts to prevent fraud in Indonesia. The research method used is qualitative research with data collection techniques through in-depth interviews with five sources who are experts in the field of forensic accounting. The results of the study show that there are four factors that encourage fraud, namely greed, opportunity, need, and disclosure or fikenel with the term GONE. Forensic accounting has a very important role in efforts to prevent fraud in Indonesia. The role of forensic accounting in fraud prevention based on these factors can be done for Greed by developing ethical policies and investigative analysis on suspicious transactions. Opportunity to develop an effective financial reporting system. Needs, in ensuring transparency and accountability in the company's financial management. Exposure is done by strengthening and developing internal audit.